Efektivitas Pendekatan Inkuiri Dalam Pembelajaran IPS Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Eva Rizkiya Safitri; Safira Wildatul Islamiyah; Annisa Syukriyah Jabrani; Oman Farhurohman (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the effectiveness of the inquiry-based learning approach in improving critical thinking skills and learning outcomes of elementary school students in Social Studies (IPS) subjects. The research method used is a library study by reviewing various national journals relevant to the topics of inquiry and Social Studies learning. The results show that the implementation of inquiry-based learning models whether in the form of social inquiry, guided inquiry, or discovery inquiry consistently has a positive impact on students’ activeness, motivation, and critical thinking abilities. The inquiry approach positions students as active subjects who construct their own understanding through questioning, observing, analyzing, and drawing conclusions. In conclusion, the inquiry model is proven effective for Social Studies learning in elementary schools as it fosters an active, meaningful learning atmosphere oriented toward the development of higher-order thinking skills.